Neonatal Diabetes Mellitus - Beltrand, Jacques; Busiah, Kanetee; Vaivre-Douret, Laurence; Fauret, Anne Laure; Berdugo, Marianne; Cavé, Hélène; Polak, Michel (Frontiers in Pediatrics, 2020)
Neonatal Diabetes (ND) mellitus is a rare genetic disease (1 in 90,000 live births). It is defined by the presence of severe hyperglycaemia associated with insufficient or no circulating insulin, occurring before the age of one year. Such hyperglycaemia requires either transient treatment with insulin in about half of cases, or permanent insulin treatment. The disease is explained by two major groups of mechanism: malformation of the pancreas with altered insulin-secreting cells development/survival or abnormal function of the existing pancreatic β cell. The most frequent genetic causes of neonatal diabetes mellitus with abnormal β cell function are abnormalities of the 6q24 locus and mutations of the ABCC8 or KCNJ11 genes coding for the potassium channel in the pancreatic β cell. Other genes are associated with pancreas malformation or destruction of β cells. Clinically, compared to patients with an ABCC8 or KCNJ11 mutation, patients with a 6q24 abnormality have lower birth weight and height, are younger at diagnosis and remission, and have a higher malformation frequency. Patients with an ABCC8 or KCNJ11 mutation have neurological and neuropsychological disorders in all those tested carefully. Up to 86% of patients having remission have recurrent diabetes when they reach puberty, with no difference due to the genetic origin. All these results reinforce the importance of prolonged follow-up by a multidisciplinary paediatric team, and later doctors specialising in adult medicine. 90% of the patients with an ABCC8 or KCNJ11 mutation as well as those with 6q24 anomalies are amenable to a successful switch from insulin injection to oral sulfonylureas.